Evidence from Albania: local government, public goods, and the free-rider problem - Lipi, Rudina; Lipi, Ilirjan; Kumi, Evis; Leskaj, Etleva (Frontiers in Political Science, 2024)
Public goods and their benefits are necessarily related to their nature. From an economic point of view, citizens are always looking for more and more public goods, judging that they should always finance them even less. Especially in a democracy, it is sufficient to remember that people who don't vote still benefit from the government's agenda. Mainly in developing countries and especially in ex-communist ones, the public does not have enough literacy and interest to understand the issues of public finance, political economy, the fiscal system, legal and political systems, social paradigms, and economics. So, it generally attributes the provision of public goods necessarily to the central and local governments without understanding or knowing any of the elements of the public goods ecosystem. So it seems that everything that the local government provides must be of high quality and be free, which proves evidence and traces of one of the main problems of public goods, which is the free-rider problem. From the research point of view, regardless of the moderation made by the civil society for the awareness of the social contract as well as the transparency of the economic activity of the municipalities, the citizens' awareness about the nature and problems of the provision of public goods still remains a concern. Therefore, the purpose of this article is to address the free-rider problem as an issue that must be recognized and considered so that optimal local legal regulations can be formulated, especially in small communities like Vlora municipality, where the free-rider problem is on a smaller scale compared to larger municipalities in the world.